A Dual-Mode Input Voltage Modulation Control Scheme for Voltage Multiplier Based X-Ray Power Supply - Iqbal, S.; Singh, G.K.; Besar, R. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
A dual-mode input voltage modulation (IVM) control scheme for a three-phase zero current switching series resonant (SR) inverter-fed three-phase voltage-multiplier based X-ray power supply is proposed to achieve a quick rise of output voltage. In this control scheme, a quasi-resonant control circuit is connected at the lower arm of the three-phase inverter to control the effective input voltage across the inverter by raising or lowering the voltage level at the lower arm of the inverter. At the startup of the power supply, the quasi-resonant control circuit shorts the lower arm of the three-phase SR inverter to ground, causing the inverter to see maximum voltage and the output voltage to rise with maximum speed toward the target voltage. As the output voltage reaches 90% of the target voltage, the effective input voltage across the inverter is reduced to a value that corresponds to the target output voltage by raising the voltage level at the lower arm of the inverter. As a result, the rise rate of the output voltage slows down and overshoot is prevented. Experimental results based on the scaled-down laboratory prototype are presented to verify the effectiveness of the proposed dual-mode IVM control scheme.